2006
DOI: 10.1186/1749-799x-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of type X collagen in a mechanically active 3-D chondrocyte culture system: a quantitative study

Abstract: Objective: Mechanical loading of cartilage influences chondrocyte metabolism and gene expression. The gene encoding type X collagen is expressed specifically by hypertrophic chondrocytes and up regulated during osteoarthritis. In this study we tested the hypothesis that the mechanical microenvironment resulting from higher levels of local strain in a three dimensional cell culture construct would lead to an increase in the expression of type X collagen mRNA by chondrocytes in those areas. Methods:Hypertrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Numerous in vitro studies in MCC and articular cartilage have shown an increase in cell differentiation and increased proteoglycan synthesis after mechanically loading the articular chondrocytes [ 35 – 39 ]. Similarly, Yang et al in their in vitro study with articular chondrocytes showed a two-fold increase in type X collagen with mechanical loading[ 40 ]. Moreover, Sobue et al showed an increase in Col2a1 and Col10a1 with 0.5N of compressive load on the MCC in mice [ 5 ].…”
Section: Discussionmentioning
confidence: 95%
“…Numerous in vitro studies in MCC and articular cartilage have shown an increase in cell differentiation and increased proteoglycan synthesis after mechanically loading the articular chondrocytes [ 35 – 39 ]. Similarly, Yang et al in their in vitro study with articular chondrocytes showed a two-fold increase in type X collagen with mechanical loading[ 40 ]. Moreover, Sobue et al showed an increase in Col2a1 and Col10a1 with 0.5N of compressive load on the MCC in mice [ 5 ].…”
Section: Discussionmentioning
confidence: 95%
“…Animal models in which growth was restricted using a wire loop [3132], physeal stapling [33], or overloading the growth plate using weighted backpacks [34] all demonstrate that the growth plate is biologically responsive to changes in physical forces. In vitro loading experiments using chondrocytes seeded in scaffolds, such as agarose, alginate, poly (L-lactide-co-ε-caprolactone (PLCL), and gelfoam all indicate that compression-induced changes in the chondrocyte’s environment modulates the synthesis of extracellular matrix components at the mRNA and protein levels [3–4, 35–38]. …”
Section: Discussionmentioning
confidence: 99%
“…This protein is expressed by hypertrophic chondrocytes at the margins of growing endochondral bones, where it provides structural support and promotes mineralization (Jacenko et al, 1993;Rosati et al, 1994). Furthermore, experiments using cultured chondrocytes show that expression of type X collagen increases in response to mechanical strain (Yang et al, 2006). In fishes, type X collagen is similarly associated with bone formation (Renn and Winkler, 2010;Eames et al, 2012).…”
Section: How Are Gill Arches Stiffened?mentioning
confidence: 99%
“…Furthermore, dynamic or cyclical mechanical forces are thought to be the predominant signals for bone growth and mineralization, and gravitational loading of inactive fish out of water (e.g. Turko et al, 2014) would be largely static and therefore may not be expected to cause a typical skeletal loading response (Turner, 1998;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%